2008
DOI: 10.1001/archdermatol.2007.45
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Nonsolar Tanning Behavior

Abstract: To develop items to measure indoor tanning and sunless tanning that can be used to monitor trends in population surveys or to assess changes in behavior in intervention studies. Design: A group of experts on indoor tanning convened in December 2005, as part of a national workshop to review the state of the evidence, define measurement issues, and develop items for ever tanned indoors, lifetime frequency, and past-year frequency for both indoor tanning and sunless tanning. Each item was subsequently assessed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…33 However, advances to improve the quality of these data are occurring by testing the criterion validity of measures of sunscreen use, cover-up behavior, sun exposure, 33 and indoor tanning 34 and whether subgroups are prone to systematic underreporting or overreporting. People of different age and occupational groups can provide relatively valid self-reports compared with objective measures.…”
Section: Measurement Of Sunburn and Sun Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 However, advances to improve the quality of these data are occurring by testing the criterion validity of measures of sunscreen use, cover-up behavior, sun exposure, 33 and indoor tanning 34 and whether subgroups are prone to systematic underreporting or overreporting. People of different age and occupational groups can provide relatively valid self-reports compared with objective measures.…”
Section: Measurement Of Sunburn and Sun Protectionmentioning
confidence: 99%
“…37 Core items to assess sunburn, sun-protection behaviors, and nonsolar tanning were recently published with demonstrated clarity and wide applicability. 32,34 The future use of these items is recommended when feasible to increase the comparability across surveys, years, and populations.…”
Section: Measurement Of Sunburn and Sun Protectionmentioning
confidence: 99%
“…Participants were asked to report the following regarding their tanning history: number of times indoor tanned in the last 12 months, number of times indoor tanned in the last 30 days, and typical hours per week sunbathed during the last summer (adapted from (Glanz et al, 2008; Lazovich et al, 2008). Participants listed each prescription and over-the-counter medications they take on a regular basis.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked about their reasons for IT the first time they went (from six choices, plus a free-response category) and who they went with the first time (from five choices, plus a freeresponse category; Lazovich et al, 2008). They were also asked about their reasons for current IT, which of the four seasons they use IT, who they go with, and how often they tanned indoors in the past 12 months.…”
Section: It Behavior and Contextmentioning
confidence: 99%
“…We chose to focus on young Caucasian women because research has demonstrated that they exhibit the highest levels of IT behavior (Guy, Berkowitz, Watson, Holman, & Richardson, 2013) and are experiencing concomitant increases in the incidence of melanoma (Purdue, Freeman, Anderson, & Tucker, 2008). engaged in the behavior over the past 12 months (Lazovich et al, 2008). Tanners and nontanners have been found to differ on various demographic and psychosocial factors, such as age (Mackay, Lowe, Edwards, & Rogers, 2007;O'Riordan et al, 2006;Stryker, Yaroch, Moser, Atienza, & Glanz, 2007), geographic region Stryker et al, 2004), beliefs about attraction (Mackay et al, 2007), vulnerability to media influences (O'Riordan et al, 2006), parents' tanning bed use (Hoerster et al, 2007;Stryker et al, 2004), and beliefs about safer tanning (Hoerster et al, 2007), to name a few.…”
mentioning
confidence: 99%